Srovnávací reklama v ČR a v zahraničí - Kurzok, Adam (2006)
The diploma thesis with the title - Comparative advertising in the Czech republic and foreign countries is focused in 20 000 words mainly on domain of unfair competition and comparative advertising in the Czech republic and takes a detailed view on current legal status, being seen in the Czech commercial law act nr. 513/1991, as well as points out some legal inaccuracies in implementing the Directive 84/450/EEC concerning misleading and comparative advertising and makes the suggestions about prospect legal amendments.